Designing English Reading Materials For Law Students - Anwar, Qosim Khoiri; Triana, Yunika; Umwari, Yvette (ELE Reviews: English Language Education Reviews, 2024)
English is a language that is generally difficult to understand for most students. Providing reading materials is one of the necessary approaches that should be undertaken by professors. This research aims to explore information regarding the needs of students in learning English and describe how reading materials for law students at a university in Indonesia are designed. The research and development (R&D) method is employed, implementing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results indicate that the majority of students greatly require materials that can enhance their reading skills. After the reading materials are designed and implemented in class, an evaluation is conducted to further develop the materials. The evaluation results, as responded to by students and expert professors, indicate that the materials align with the students’ needs. The average percentage of students’ needs fulfilled by the reading materials is 84%, while the average assessment percentage from the experts is 90.4%. This demonstrates that the reading materials are valid for use as English learning materials for law students.